Intravenous Fluid Prescription Practices in Critically Ill Children: A Shift in Focus from Natremia to Chloremia? - Bulfon, Adrian F.; Alomani, Hakem L.; Anton, Natalie; Comrie, Brooke T.; Rochwerg, Bram; Stef, Sorina A.; Thabane, Lehana; Vanniyasingam, Thuva; Choong, Karen (Journal of Pediatric Intensive Care, 2019)
Our objective is to evaluate intravenous (IV) fluid prescription practice patterns in critically ill children in the first 72 hours of pediatric intensive care unit (PICU) admission and to evaluate the incidence and predictors of hyperchloremic metabolic acidemia (HCMA) and the association between HCMA and adverse outcomes. This retrospective cohort study was conducted in two tertiary-care Canadian PICUs. Children aged 0 to 18 years admitted to the PICU between January 2015 and January 2016 who received at least 50% of their calculated maintenance fluid requirements parenterally during the first 24 hours of admission were included. Children with known preexisting conditions associated with HCMA, such as renal tubular acidosis and gastrointestinal bicarbonate losses, were excluded. Of the 771 children screened, 543 met eligibility criteria and were included. The commonest prescribed maintenance fluid was 0.9% NaCl (72.9%) followed by lactated Ringer's solution (19.6%) and hypotonic solutions (4.6%). Balanced salt solutions (i.e., lactated Ringer's and Plasma-Lyte) were as commonly administered as unbalanced solutions (0.9% NaCl) for volume expansion (49.6 vs. 48.5%, respectively). Medications contributed to a significant proportion of total daily intake, in excess of bolus fluids. The incidence of hyperchloremia and HCMA was 94.9% (95% confidence interval [CI]: 93.2–96.9; 470/495) and 38.9% (95% CI: 34.6–43.2; 196/504), respectively. Predictors of HCMA were increasing combined bolus and maintenance 0.9% NaCl intake (odds ratio: 1.13; 95% CI: 1.04–1.23) and increasing severity of illness. HCMA was not associated with an increased risk of acute kidney injury, feeding intolerance, or PICU-acquired weakness. Isotonic fluids, specifically 0.9% NaCl, were the most commonly administered maintenance IV fluid in critically ill children. Sources of chloride load are not isolated to resuscitation fluids as previously suggested. Maintenance fluids and fluids administered with medications and IV flushes (fluid creep) are under-recognized significant sources of fluid and electrolyte intake in critically ill children. HCMA is common, and further prospective research is required to determine whether HCMA is indeed harmful in children. However, all significant sources of fluid should be accounted for in the design of future trials comparing balanced and unbalanced salt solutions.
Keywords: pediatrics; IV solutions; maintenance fluids; hyperchloremia; acidosis